2006
DOI: 10.1016/j.brainres.2006.02.136
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS-1 and -4 are up-regulated following transient middle cerebral artery occlusion in the rat and their expression is modulated by TNF in cultured astrocytes

Abstract: ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) enzymes are a recently described group of metalloproteinases. The substrates degraded by ADAMTS-1, -4 and -5 suggests that they play a role in turnover of extracellular matrix in the central nervous system (CNS). ADAMTS-1 is also known to exhibit anti-angiogenic activity. Their main endogenous inhibitor is tissue inhibitor of metalloproteinases (TIMP)-3.The present study was designed to investigate ADAMTS-1, -4 and -5 and TIMP-3 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 46 publications
(53 reference statements)
4
45
0
Order By: Relevance
“…Illustrated by atherosclerosis, many inflammatory diseases comprise extracellular matrix remodeling processes that are regulated at different levels by proinflammatory cytokines such as IL-1␤ and TNF-␣ and require metalloproteinase activity. IL-1␤ and TNF-␣ are known to induce Adamts-1 mRNA in different cell types (57,58); however, the precise transcriptional mechanism involved awaits identification. Similar to Ang-II, we have identified C/EBP␤ as the chief mediator of Adamts-1 regulation by IL-1␤ and TNF-␣ in vascular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Illustrated by atherosclerosis, many inflammatory diseases comprise extracellular matrix remodeling processes that are regulated at different levels by proinflammatory cytokines such as IL-1␤ and TNF-␣ and require metalloproteinase activity. IL-1␤ and TNF-␣ are known to induce Adamts-1 mRNA in different cell types (57,58); however, the precise transcriptional mechanism involved awaits identification. Similar to Ang-II, we have identified C/EBP␤ as the chief mediator of Adamts-1 regulation by IL-1␤ and TNF-␣ in vascular cells.…”
Section: Discussionmentioning
confidence: 99%
“…After a kainateinduced excitotoxic insult, a transient up-regulation of ADAMTS-4 and ADAMTS-1 coincides with a marked increase of brevican proteolysis (Mayer et al 2005;Yuan et al 2002). A similar reaction is also observed in an experimental model of cerebral ischemia (Cross et al 2006). Moreover, motor axon disruption induces the ADAMTS-1 production in the aVected neurons and there is growing evidence that the same enzyme is also over-expressed in association with various neurodegenerative disorders (Miguel et al 2005;Satoh et al 2000).…”
Section: Matrix Turnovermentioning
confidence: 92%
“…Bevitt et al (29) reported that ADAMTS1 was induced by TNF␣ stimulation in ARPE. Cross et al (30) reported that ADAMTS1 mRNA was increased by IL-1␤ and TNF in cultured astrocytes; however, Kalinski et al (31) reported that ADAMTS1 mRNA was decreased by IL-1␤ in the human chondrosarcoma cell line C3842. In fact, we have previously reported that IL-1␤ stimulation rather decreased ADAMTS1 mRNA in another chondrosarcoma cell line, OUMS-27 (32).…”
Section: Discussionmentioning
confidence: 99%